Implications of WHO COVID-19 interim guideline 2020.5 on the comprehensive care for infected persons in Africa Before, during and after clinical management of cases (2022)
The novel coronavirus disease 2019 (COVID-19) is one of the biggest public health crises globally. Although Africa did not display the worst-case scenario compared to other continents, fears were still at its peak since Africa was already suffering from a heavy load of other life-threatening infectious diseases such as HIV/AIDS and malaria. Other factors that were anticipated to complicate Africa’s outcomes include the lack of resources for diagnosis and contact tracing along with the low capacity of specialized management facilities per capita. The current review aims at assessing and generating discussions on the realities, and pros and cons of the WHO COVID-19 interim guidance 2020.5 considering the known peculiarities of the African continent. A comprehensive evaluation was done for COVID-19-related data published across PubMed and Google Scholar (date of the last search: August 17, 2020) with emphasis on clinical management and psychosocial aspects. Predefined filters were then applied in data screening as detailed in the methods. Specifically, we interrogated the WHO 2020.5 guideline viz-a-viz health priority and health financing in Africa, COVID-19 case contact tracing and risk assessment, clinical management of COVID-19 cases as well as strategies for tackling stigmatization and psychosocial challenges encountered by COVID-19 survivors. The outcomes of this work provide links between these vital sub-themes which may impact the containment and management of COVID-19 cases in Africa in the long-term. The chief recommendation of the current study is the necessity of prudent filtration of the global findings along with regional modelling of the global care guidelines for acting properly in response to this health threat on the regional level without exposing our populations to further unnecessary adversities.